Medications to reduce breast cancer risk: a network meta-analysis of randomized controlled trials - Ghazaleh Pourali; Minglu Liu; Supriya S. Sherpa; Angela Hardi; Chongliang Luo; Adetunji T. Toriola (Breast Cancer Research)
Abstract Background Given the rising incidence of breast cancer, especially in premenopausal women, there is an urgent need to identify additional risk-reducing medications to accelerate prevention, as only a few are currently approved. We, therefore, performed network meta-analysis (NMA) to identify and compare the efficacy of medications for primary breast cancer prevention. Methods We performed a literature search completed on November 16, 2023, in Embase, Ovid-Medline, Scopus, and Cochrane Library for randomized controlled trials (RCTs) evaluating risk-reducing medications in women without a history of invasive breast cancer. Two reviewers independently screened and extracted data based on predefined criteria, following the Preferred Reporting Items for Systematic reviews and Meta-Analyses guidelines, and assessed the risk of bias using the Revised Cochrane Risk of Bias tool. The primary outcome was overall breast cancer incidence, with secondary outcomes including invasive breast cancer and ductal carcinoma in situ. NMA was performed using a random-effects model, measuring efficacy with risk ratios (RR) and number needed to treat (NNT). Medications were ranked using the Surface Under the Cumulative RAnking curve (SUCRA). We performed subgroup analyses by menopause status, primary versus secondary/other outcomes, follow-up, and intervention duration. Results Out of 8,598 studies screened, 43 RCTs (n = 337,240 women) met inclusion criteria. Six medications reduced overall breast cancer risk compared to placebo: sulfonylurea (RR = 0.18, 95% CI = 0.04–0.91, NNT = 44.1, SUCRA = 0.90), thiazolidinediones (RR = 0.25, 95% CI = 0.08–0.78, NNT = 48.3, SUCRA = 0.80), third-generation selective estrogen receptor modulators (SERMs) (RR = 0.46, 95% CI = 0.33–0.66, NNT = 67.3, SUCRA = 0.62), aromatase inhibitors (AIs) (RR = 0.50, 95% CI = 0.39–0.66, NNT = 73.0, SUCRA = 0.55), raloxifene (RR = 0.63, 95% CI = 0.47–0.84, NNT = 96.9, SUCRA = 0.37), and tamoxifen (RR = 0.76, 95% CI = 0.65–0.88, NNT = 149.7, SUCRA = 0.23). AIs (RR = 0.48, 95% CI = 0.33–0.71), tamoxifen (RR = 0.63, 95% CI = 0.51–0.78), and raloxifene (RR = 0.63, 95% CI = 0.47–0.86), were effective for invasive breast cancer. Third-generation SERMs (RR = 0.46, 95% CI = 0.32–0.67), AIs (RR = 0.51, 95% CI = 0.40–0.64), raloxifene (RR = 0.61, 95% CI = 0.46–0.82), and tamoxifen (RR = 0.76, 95% CI = 0.66–0.86) were effective in studies with breast cancer as a primary outcome, while thiazolidinediones (RR = 0.25, 95% CI = 0.07–0.84) were effective in studies with breast cancer as a secondary/other outcome. Conclusions This NMA confirms the efficacy of tamoxifen, raloxifene, and AIs, and identifies thiazolidinediones and third-generation SERMs as promising agents for breast cancer prevention, though not currently included in guidelines. These findings extend prior evidence and highlight the need for trials in premenopausal and racially diverse populations to address existing gaps.